Work-Life Balance among Generation Z: The Role of Workload, Social Support, and Work Flexibility - Rashaky Arya Vito; Aslam Mei Nur Widigdo (Universitas Mercu Buana, 2026)
This study examines the influence of workload, social support, and work flexibility on work–life balance among Generation Z employees in Jakarta using the JD-R framework. The target population comprised employees aged 19–28 years. Given the indeterminate population size, the sample was determined using the rule of thumb of at least five respondents per indicator. With 27 indicators, the minimum required sample was 135, and 150 valid responses were obtained through an online survey. Data were analyzed using PLS-SEM with SmartPLS software.Findings reveal that workload exerts a significant negative effect on work-life balance, whereas social support and work flexibility demonstrate significant positive effects. Social support emerges as the most dominant predictor. A key insight is that Gen Z employees tend to rely more on relational resources than structural resources in maintaining work–life balance, a pattern influenced by Indonesia’s collectivistic cultural context.This study extends the JD-R framework by emphasizing the context-dependent nature of job resources. Practically, organizations should balance workload management with the development of supportive and flexible work environments. The study is limited by its cross-sectional design and specific urban context, suggesting the need for longitudinal and broader future research.